2016
DOI: 10.1590/1676-0611-bn-2014-0182
|View full text |Cite
|
Sign up to set email alerts
|

Wild vertebrate roadkill in the Chapada dos Veadeiros National Park, Central Brazil

Abstract: Chapada dos Veadeiros National Park is one of the most important protected areas of the Brazilian Cerrado and is inhabited by diverse species, but the area has seldom been studied. From 2006 to 2008, we studied the impact of roads on wild vertebrates by recording roadkill on the two main roads located in the vicinity of the park. Of 824 killed vertebrates belonging to 138 species that were recorded, the species that were found most often in each vertebrate group were the Schneider's toad (Rhinella schneideri),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
0
22
2
5
Order By: Relevance
“…In Europe, USA and Canada some studies tried to understand this (CLEVENGER et al, 2003;GRILO et al, 2009;GRILO et al, 2012;D'AMICO et al, 2015;GARRIGA et al, 2017) and concluded that temperature influences roadkill (D'AMICO et al, 2015;GARRIGA et al, 2017). In Brazil, we have just started, our researches investigate if there are more roadkill in the rainy or dry season (BUENO; ALMEIDA, 2010;RAMOS et al, 2011;BRAZ;FRANÇA, 2016) or the stretches of the highway with higher roadkill rates (CÁCERES et al, 2012;BUENO et al, 2012;SANTANA, 2012;FERREIRA et al, 2014;CARVALHO et al, 2015;ASCENSÃO et al, 2017;SANTOS et al, 2017). We still need to understand better the influence of climate variables on roadkill in tropical countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Europe, USA and Canada some studies tried to understand this (CLEVENGER et al, 2003;GRILO et al, 2009;GRILO et al, 2012;D'AMICO et al, 2015;GARRIGA et al, 2017) and concluded that temperature influences roadkill (D'AMICO et al, 2015;GARRIGA et al, 2017). In Brazil, we have just started, our researches investigate if there are more roadkill in the rainy or dry season (BUENO; ALMEIDA, 2010;RAMOS et al, 2011;BRAZ;FRANÇA, 2016) or the stretches of the highway with higher roadkill rates (CÁCERES et al, 2012;BUENO et al, 2012;SANTANA, 2012;FERREIRA et al, 2014;CARVALHO et al, 2015;ASCENSÃO et al, 2017;SANTOS et al, 2017). We still need to understand better the influence of climate variables on roadkill in tropical countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These authors believe that there is an increase in roadkill accidents in the dry season due to lack of resources, which would increase the mobility of animals and, consequently, the roadkill rates on highways. On the other hand, some authors have found no difference on vertebrate roadkill rates between seasons (MILLI; PASSAMANI, 2006;HENGEMÜHLE;CADEMARTORI 2008;CUNHA et al, 2010) or a higher roadkill rate in the wet season (BRAZ;FRANÇA, 2016). Still, the majority of the studies investigate the vertebrates as a group or examine mammals alone.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibians are one of the most underestimated taxa in road kill surveys (Teixeira et al, 2013, Braz & França, 2016. In the present survey, it was possible to identify only one individual of Rhinella sp., due to its outstanding size.…”
Section: Resultsmentioning
confidence: 74%
“…In the present survey, it was possible to identify only one individual of Rhinella sp., due to its outstanding size. Accordingly, to Corrêa et al (2013), other species of smaller amphibians occur in the region and most likely, the number of road killed frogs was probably once again underestimated (Teixeira et al, 2013, Braz & França, 2016.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation